European Food Safety Certification - The “GlobalGAP” Standard and its Accredited Certification Program - Richard C. Yudin; Keith R. Schneider (EDIS)
FSHN-08-01, a 5-page fact sheet by Richard C. Yudin and Keith R. Schneider, informs growers in Florida and elsewhere about this standard for agricultural products exported to the European Union, Switzerland, and Norway. Includes references. Published by the UF Department of Food Science and Human Nutrition, February 2008.